2013
DOI: 10.2337/db12-1220
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Rescue of Obese Adipose-Derived Stem Cells by Lin28/Let7 Pathway

Abstract: Adipose-derived stem cells (ASCs) are promising candidates for autologous cell-based regeneration therapies by virtue of their multilineage differentiation potential and immunogenicity; however, relatively little is known about their role in adipose tissue physiology and dysfunction. Here we evaluated whether ASCs isolated from nonobese and obese tissue differed in their metabolic characteristics and differentiation potential. During differentiation to mature adipocytes, mouse and human ASCs derived from nonob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 46 publications
2
66
0
Order By: Relevance
“…We have defined hASCs according to these criteria [20][21][22]. Other methods have been frequently used to identify, isolate, and characterize human and murine ASCs from adipose tissue [23,38]. Thus, previous studies have reported that human and murine WAT is a rich reservoir of CD45 -CD34 + ASCs, with a high basal migration capacity in lean-derived, but not obese-derived, ASCs [23,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have defined hASCs according to these criteria [20][21][22]. Other methods have been frequently used to identify, isolate, and characterize human and murine ASCs from adipose tissue [23,38]. Thus, previous studies have reported that human and murine WAT is a rich reservoir of CD45 -CD34 + ASCs, with a high basal migration capacity in lean-derived, but not obese-derived, ASCs [23,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous results demonstrated that the metabolic phenotype of CD34 + MSCs isolated from obese adipose tissue significantly differed from equivalent cells isolated from lean adipose tissue [23]. To question whether an obese environment might similarly affect the plasticity of isolated hASCs, we evaluated proliferation, migration, and differentiation capacity of hASCs obtained from lean and obese individuals.…”
Section: Obesity Disturbs Hascs Plasticity and Immunophenotypic Profilementioning
confidence: 96%
“…Additionally, LIN28 regulates glucose metabolism; its overexpression increases the ability of muscle cells to take up glucose (Zhu et al, 2010), while its loss results in insulin resistance Zhu et al, 2011). Furthermore, sensitivity to insulin can be restored in obese adipose stem cells with the introduction of LIN28 (Perez et al, 2013). Finally, LIN28 overexpression increases regeneration during digit repair, epidermal hair regrowth and pinnal tissue regrowth in the mouse (Shyh- Chang et al, 2013).…”
Section: Developmental and Physiological Roles For Lin28mentioning
confidence: 99%
“…Initial investigations have revealed roles for LIN28 in glucose uptake and tolerance, diabetes, sickle cell anemia and cancer (de Vasconcellos et al, 2014;Perez et al, 2013;Shinoda et al, 2013;Shyh-Chang et al, 2013;Zhu et al, 2011), suggesting that the modulation of LIN28 activity might be an attractive therapeutic approach. For example, the expression of LIN28 in cultured, sickle-shaped erythrocytes resulted in a significant decrease in their sickle morphology compared with control erythrocytes (de Vasconcellos et al, 2014).…”
Section: Lin28 In Disease and Therapymentioning
confidence: 99%
“…These phenomena occurred in part through let-7-mediated repression of multiple components of the insulin-PI3K-mTOR pathway [60]. Furthermore, it was recently shown that Lin28 restores glucose metabolism in obese adipocyte stem cells through repression of let-7 expression [61]. MiR-29a…”
Section: Mirna Regulation Of Insulin Secretion and Signalingmentioning
confidence: 99%